Multilevel Safety Communication Patterns in High-Risk Glass Manufacturing: An Empirical Study of Formal, Informal, and Symbolic Channels at PT Asahimas Flat Glass Tbk - Fadli Muhammad Athalarik; Puji Lestari; Hari Eko Irianto (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze formal, informal, and symbolic OHS communication patterns across organizational levels at PT Asahimas Flat Glass Tbk and to construct the first empirically grounded, channel-specific multilevel OHS communication model for glass manufacturing operationalized through the Convergence Model in a Southeast Asian high-risk industrial context. A constructivist qualitative case study design was employed with 14 purposively sampled informants spanning managerial to operational levels; data were collected through in-depth interviews, observation of nine communication events, and document analysis, then coded in NVivo using grounded theory open, axial, and selective coding procedures with source and technique triangulation throughout. The findings of this study reveal a multilevel OHS communication architecture integrating cascading formal policy directives and ritualized daily Toolbox Meetings as the primary transmission mechanism, informal interpersonal channels bridging hierarchical formality with behavioral internalization, and digital reporting via the My Asahimas application raising participation from 79% to 97% among 889 employees by addressing the culturally embedded barrier of sungkan through anonymization—with the core phenomenon identified as safety culture internalization through a multilevel guerrilla communication strategy. The contribution of this study is the SHIFT Model (Safety Habituation through Interactive and Formal Transformation), the first indigenous five-stage model empirically grounding safety culture internalization in Indonesian glass manufacturing, while simultaneously advancing Convergence Model theory in Southeast Asian high-risk industrial contexts and providing practitioners with a diagnostic framework for identifying and addressing internalization regression at each stage of safety culture transformation.